PENCAPAIAN TUGAS PERKEMBANGAN REMAJA AWAL - Yolla Ade Putri; Rosmawati '; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Not optimal achievement of early adolescent development tasks at school. Therefore, researchers feel the need to examine the task of student development. The formulation of the problem in this research are: 1) how the achievement of the students 'overall development task 2) how to describe the achievement of the students' developmental achievement 3) how to describe the achievement of female students. The purpose of this study was to determine the level of achievement of early adolescent developmental tasks. The method used in this research is using descriptive quantitative. To collect data about the achievement of developmental tasks used inventory instrument development task Universitas Pendidikan Indonesia (UPI.2003).Keywords: Early Teen Development Tasks